The Role of BMT Al-Istiqamah Sharia Cooperative in Improving Micro-Economy - Nur, Ermin; Zubair, Muhammad Kamal (Al-Iftah: Journal of Islamic studies and society, 2020)
This study examines BMT (Baitul Mal WaTamwil) Al-Istiqamah in improving micro-economy in Enrekang. The purpose of this study was to determine the strategic role of BMT Al-Istiqamah in improving micro-economy. This type of research is qualitative with a managerial approach and Islamic economics; the research paradigm is direct involvement and intense interaction with informants; data sources are empirical data obtained in the field through the Founding Board, Manager, Members and BMT Al-Istiqamah customers' and Enrekang district government as primary sources, as well as the documents and books relating to research as secondary data . The result of this study indicated that BMT Al-Istiqamah took part in improving micro-economy in Enrekang. The role played by BMT Al-Istiqamah was the role of empowering human resources and an entrepreneurial spirit, the role of improving the welfare of the micro economy, and the role of alienating people from usury practices. The result of this study also indicated that the factors supporting the success of BMT Al-Istiqamah. The internal support to the microeconomics were strategic location, commitment of the board of directors, management and members, and high participation of members' savings, while the external support were the high demand of micro entrepreneurs to BMT al-Istiqamah, the ease of getting venture capital assistance felt by micro businesses, and government support.